SCoPE - Baldissera, Thais A. (2019)
info:eu-repo/grantAgreement/FCT/5876/147324/PT This work has been partially funded by the Center of Technology and Systems (CTS) and the Portuguese FCT-PEST program UID/EEA/00066/2013 (Impactor project), and by CAPES (n. 9087-3) and Instituto Federal Farroupilha (Brazil).